1985
DOI: 10.1073/pnas.82.15.5170
|View full text |Cite
|
Sign up to set email alerts
|

Hemin inhibits internalization of transferrin by reticulocytes and promotes phosphorylation of the membrane transferrin receptor.

Abstract: Addition of hemin to reticulocytes inhibits incorporation of iron from transferrin [Ponka, P. & Neuwirt, J. (1969) Blood 33,. Heme also regulates protein synthesis in immature erythroid cells through its effects on phosphorylation of the initiation factor eIF-2. We have therefore examined its effects on endocytosis of iron-transferrin and phosphorylation of the transferrin receptor. Hemin gM) reduced iron transport but increased cell-associated transferrin. When intracellular iron delivery was inhibited by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…Studies on the transferrin receptor (May et al, 1984;Cox et al, 1985) and on the type I1 insulin-like growth factor receptor (Corvera and Czech, 1985) have suggested that increased phosphorylation of those receptors might affect the process of internalization. We have shown, however, that a n anti-EGF receptor mAb elicited rapid receptor internalization into endosomes without stimulating receptor phosphorylation (Sunada et al, 1986).…”
mentioning
confidence: 99%
“…Studies on the transferrin receptor (May et al, 1984;Cox et al, 1985) and on the type I1 insulin-like growth factor receptor (Corvera and Czech, 1985) have suggested that increased phosphorylation of those receptors might affect the process of internalization. We have shown, however, that a n anti-EGF receptor mAb elicited rapid receptor internalization into endosomes without stimulating receptor phosphorylation (Sunada et al, 1986).…”
mentioning
confidence: 99%
“…First, ALAS2, the erythroid-specific form of ALAS, contains an IRE in the 5′ UTR258, 259 and neither its synthesis nor its activity is inhibited by heme260. In reticulocytes, heme inhibits the internalization of transferrin by TfR1261, 262. The non-IRE form of DMT1 dominates in reticulocytes and is found on the membranes of endosomes containing TfR1263.…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that haem inhibits either iron (Ponka et al, 1974) or bicarbonate (Schulman et al, 1974b) release from transferrin; however, the release of both are probably inhibited by the same mechanism, since iron release from transferrin is accompanied by the release of bicarbonate, and vice versa (Schulman et al, 1974b;Martinez-Medellin & Schulman, 1973). More recently it has been suggested that haem inhibits the internalization of transferrin by reticulocytes (Tacopetta & Morgan, 1984;Cox et al, 1985), but the results of the present study indicate that this is probably not the primary site of haem action. We demonstrated that, at low concentrations, haem inhibits cellular iron uptake and even more its incorporation into haem, but does not inhibit the initial rate of transferrin uptake or the internalization of transferrin by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that haem is a feedback regulator of haem synthesis in erythroid cells (London , 1964;Ponka & Neuwirt, 1969), and although there is no doubt that haem inhibits haem synthesis in reticulocytes (Ponka et al, 1974;Schulman et al, 1974b;Morgan, 1981;Iacopetta & Morgan, 1984;Cox et al, 1985;Ponka & Schulman, 1985a), in which it can affect only post-transcriptional processes, there has been controversy conceming the mechanism involved. The original (London et al, 1964) and widely held view (Ibraham et al, 1983) is that haem feedback-inhibits the first enzyme in the haem-biosynthetic pathway, namely 6-aminolaevulinic acid synthase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation